Blockade of CD40/CD40 ligand interactions attenuates skin fibrosis and autoimmunity in the tight-skin mouse. Issue 6 (6th September 2007) - Komura, K; Fujimoto, M; Yanaba, K; Matsushita, T; Matsushita, Y; Horikawa, M; Ogawa, F; Shimizu, K; Hasegawa, M; Takehara, K; Sato, S
Abstract : Objective: : To assess the association of CD40/CD40 ligand (CD40L) interactions with the development of skin fibrosis and autoimmunity in tight-skin (TSK/+) mouse, which is a mouse model for human systemic sclerosis. Methods: Newly born TSK/+ mice were treated with murine anti-CD40L monoclonal antibody (100 μg intraperitoneally weekly). Hypodermal thickness of 8-week-old female mice (defined as the thickness of a subcutaneous loose connective tissue layer beneath the panniculus carnosus) was measured under a light microscope. All skin sections were taken from the para-midline, upper back region. Serum anti-topoisomerase I autoantibody levels, serum immunoglobulin levels and plasma soluble CD40L levels were determined by enzyme-linked immunosorbent assay. For analysis of lymphocyte surface molecules, single cell suspensions of lymphocytes were stained by monoclonal antibodies. Proliferation of TSK/+ B cells and fibroblasts to anti-CD40 antibodies was assessed by the uptake of [3 H]-labelled thymidine and bromodeoxyuridine, respectively. Results: The blockade of CD40/CD40L interactions by anti-CD40L monoclonal antibody significantly reduced cutaneous fibrosis (65%) and anti-topoisomerase I autoantibody in TSK/+ mice. Anti-CD40L monoclonal antibody also normalised B lymphocyte abnormal activation in TSK/+ mice, demonstrated by hyper-γ-globulinaemia. Furthermore, augmented CD40/CD40L interactions in TSK/+ mice were suggested by upregulated expression of CD40L on CD4 + T cells, elevated plasma soluble CD40L levels. The hyperresponsiveness to CD40 stimulation was also observed in TSK/+ B cells and fibroblasts. Conclusions: Cutaneous fibrosis and autoimmunity in TSK/+ mice are closely correlated with CD40/CD40L interactions.